On optical solitons of the non-local NLSE with time dependent coefficients - Baleanu, Dumitru; Kilic, Bulent; İnç, Mustafa (Natl Inst Optoelectronics, 2016)
This paper integrates non-local nonlinear Schrodinger equation (NNLSE) with time dependent coefficients. The first integral method (FIM) is applied to report the optical soliton solutions of NNLSE with parabolic law nonlinearity and time dependent coefficients which are the terms of velocity dipersion, linear and nonlinear terms and also non-local one.
Keywords: FIM; NNLSE; Optical soliton solutions